Baseline connectome modular abnormalities in the childhood phase of a longitudinal study on individuals with chromosome 22q11.2 deletion syndrome. Issue 1 (8th October 2017) - Zhan, Liang; Jenkins, Lisanne M.; Zhang, Aifeng; Conte, Giorgio; Forbes, Angus; Harvey, Danielle; Angkustsiri, Kathleen; Goodrich‐Hunsaker, Naomi J.; Durdle, Courtney; Lee, Aaron; Schumann, Cyndi; Carmichael, Owen; et al.
Abstract: Occurring in at least 1 in 3, 000 live births, chromosome 22q11.2 deletion syndrome (22q11DS) produces a complex phenotype that includes a constellation of medical complications such as congenital cardiac defects, immune deficiency, velopharyngeal dysfunction, and characteristic facial dysmorphic features. There is also an increased incidence of psychiatric diagnosis, especially intellectual disability and ADHD in childhood, lifelong anxiety, and a strikingly high rate of schizophrenia spectrum disorders, which occur in around 30% of adults with 22q11DS. Using innovative computational connectomics, we studied how 22q11DS affects high‐level network signatures of hierarchical modularity and its intrinsic geometry in 55 children with confirmed 22q11DS and 27 Typically Developing (TD) children. Results identified 3 subgroups within our 22q11DS sample using a K‐means clustering approach based on several midline structural measures‐of‐interests. Each subgroup exhibited distinct patterns of connectome abnormalities. Subtype 1, containing individuals with generally healthy‐looking brains, exhibited no significant differences in either modularity or intrinsic geometry when compared with TD. By contrast, the more anomalous 22q11DS Subtypes 2 and 3 brains revealed significant modular differences in the right hemisphere, while Subtype 3 (the most anomalous anatomy) further exhibited significantly abnormal connectome intrinsic geometry in the form of left–right temporal disintegration. Taken together, our findings supported an overall picture of (a) anterior‐posteriorly differential interlobar frontotemporal/frontoparietal dysconnectivity in Subtypes 2 and 3 and (b) differential intralobar dysconnectivity in Subtype 3. Our ongoing studies are focusing on whether these subtypes and their connnectome signatures might be valid biomarkers for predicting the degree of psychosis‐proneness risk found in 22q11DS. Hum Brain Mapp 39:232–248, 2018 . ©2017 Wiley Periodicals, Inc.